Case Report: Ehrlichiosis and Anaplasmosis in Timber Wolf Crossbreed (Canis lupus) in Bali, Indonesia - Widyasanti, Ni Wayan Helpina; Putra, I Putu Cahyadi; Suwiti, Ni Ketut (Media Kedokteran Hewan, 2025)
Pathogenic bacteria from the Anaplasmataceae family cause ehrlichiosis and anaplasmosis in animals, including dogs and wild carnivores (wolves, foxes, raccoons, and others). These diseases are emerging vector-borne diseases transmitted through ticks. A six-month-old timber wolf crossbreed (Canis lupus) came to the Veterinary Teaching Hospital, Faculty of Veterinary Medicine, Udayana University, Bali, Indonesia, with a history of weakness, decreased appetite, and excessive salivation. Examination revealed that the timber wolf crossbreed had pale mucosa, lethargy, hypersalivation, normochromic microcytic anemia, thrombocytopenia, gas accumulation in the stomach and intestine, and no foreign bodies in the digestive tract. Rapid test results with the SNAP® 4Dx® Plus Test IDEXX® were positive for Ehrlichia sp. and Anaplasma sp.; however, the blood smear examination was negative. The therapy for this case included sodium chloride 0,9% infusion as fluid therapy, atropine sulfate as symptomatic therapy, hematopoietic, multivitamin, iron supplementation as supportive therapy, and doxycycline antibiotic as causative therapy. The wolf showed decreased salivary excretion and ate 4 h after fluid therapy, atropine sulfate, and hematopoietic administration. The wolf improved their condition through increased appetite and became agile after seven days of treatment. The wolf was declared clinically cured after two weeks of doxycycline treatment.